2008
DOI: 10.1007/s11104-008-9712-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on growth, ion accumulation and the roles of ions in osmotic adjustment of two populations of Suaeda salsa

Abstract: The effect of salinity on growth, ion accumulation and the roles of ions in osmotic adjustment of two populations of Suaeda salsa were investigated. Seeds were collected from an intertidal zone or a saline inland zone in the Yellow River Delta in Shandong province, China. Seedlings were exposed to 10, 100, 200, 400 or 600 mM NaCl for 18 days in a greenhouse. NO 3 − concentration in the soil where S. salsa grows in an intertidal zone was much lower than that for the second population, but leaf NO 3 − concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 33 publications
4
61
0
Order By: Relevance
“…Similarly in a field investigation, the root/shoot ratio of S. salsa from the intertidal zone was higher than that in the inland population (Table 1). S. salsa from the intertidal zone shows much fewer main stem branches and lower shoot dry mass compared with S. salsa from saline inland in older seedling stage (Song et al 2009), and similar result was shown from a field investigation (Liu 2006). The tide is one challenge for S. salsa growing in the intertidal zone during their germination and seedling stages.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly in a field investigation, the root/shoot ratio of S. salsa from the intertidal zone was higher than that in the inland population (Table 1). S. salsa from the intertidal zone shows much fewer main stem branches and lower shoot dry mass compared with S. salsa from saline inland in older seedling stage (Song et al 2009), and similar result was shown from a field investigation (Liu 2006). The tide is one challenge for S. salsa growing in the intertidal zone during their germination and seedling stages.…”
Section: Discussionsupporting
confidence: 78%
“…Salinity damages plants mainly through the osmotic effect, the effect of specific ion toxicity and subsequently through nutritional stress (Song et al, 2009). In order to fight with the stress effects, the plants make materials which adjust osmotic pressure and accumulate them.…”
Section: Introductionmentioning
confidence: 99%
“…Meloni et al (2008) reported that resistance to salt is correlated negatively with Na + concentration and positively with K + concentration. Also, high K + /Na + in plant tissues, has been considered as an important physiological solution for salinity tolerance in some plants (Meloni et al, 2008;Song et al, 2009). Since different plants react to salinity in different ways, therefore, the study of salinity tolerance mechanisms in plants is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Four-week-old seedlings were transferred to hydroponic culture containers in half strength Hoagland's solution, which were changed daily, 12 plants were placed in each container filled with 1000 mL solution. After a week, the seedlings were treated with half strength Hoagland's solution containing 0, 100,150, 200, 300 mM NaCl (pH 6.12 ± 0.08) and 0, 50, 100, 150, 200 mM NaHCO 3 (pH 8.37 ± 0.15), the concentrations setting refer to previous studies on S.salsa, S. maritime and S. glauca (Flowers et al 1976;Song et al 2009). Five independent biological replicates were used in physiological analysis.…”
Section: Methodsmentioning
confidence: 99%